Forming of regional legal reputation rating company - Olesia Khokhuliak (Cхід, 2014)
In the article the review of modern methodological approaches is carried out to forming of the reputation rating of legal companies and their features are considered. Except practice of western rating legal directories that successfully work at the market of legal services, methodology of the Russian and home rating directories is considered. Semantic interpretation is conducted and the matrix of criteria of the reputation rating of legal firms of basic rating directories is formed: Chambers, Legal 500, FLR Who's, Вest Lawyers, Who Legal, Pravo.Ru, GVardia of legal companies. The row of conclusions that touch possibilities and expediency of application of rating technologies in the estimation of regional market of legal services is formed. Development of the regional rating of legal firms will allow really to estimate the contribution of large operators to regional market of legal services development, will provide possibility to the small regional companies to go out on the new level of business activity. Also it will be the catalyst of introduction of the new service technologies of service oriented to the client, will assist to development of competition on regional to the market.